2014
DOI: 10.5601/jelem.2014.19.2.670
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and biological properties of composts produced from organic waste

Abstract: The aim of the investigations was to determine the effect of composting municipal waste with various added substances (starch, edible oil or urea) on the content of selected forms of zinc, cadmium, copper and lead, the quality of organic matter and counts of some groups of physiological microorganisms. The above properties of compost may provide the basis for assessment of the composting process efficiency. The research object was biomass prepared from plant and other biodegradable waste generated in the area … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…The content of organic carbon in organic waste compost can be determined by using oxidation-titration with ferrous ammonium sulfate method followed by the process of mineralization in potassium dichromate [33]. The nitrogen content in the organic waste compost is determined by using the Kjeldahl method.…”
Section: Factors Affecting the Organic Waste Compostmentioning
confidence: 99%
“…The content of organic carbon in organic waste compost can be determined by using oxidation-titration with ferrous ammonium sulfate method followed by the process of mineralization in potassium dichromate [33]. The nitrogen content in the organic waste compost is determined by using the Kjeldahl method.…”
Section: Factors Affecting the Organic Waste Compostmentioning
confidence: 99%
“…Studies carried out by Chen et al (1996) and Drozd et al (2004) indicate there are pH changes during the composting process. The value of this parameter in the final phases is close or slightly higher than the initial value (Gondek et al 2014), whereas during maturation, small changes in pH are usually observed. These changes result from different intensities of biochemical processes occurring during composting, which depend mainly on maturing compost temperature, oxygen content and humidity.…”
Section: Resultsmentioning
confidence: 74%
“…The majority of these toxic metals accumulate in the sludge, since only a small amount is released with the treated final effluent (Sorme and Lagerkvist, 2002). Once sludge from WWTPs are applied to the soil, the degradation of organic compounds in sewage sludge affects the availability of heavy metals, inducing accumulation in plant biomass, one of the primary elements of the human food chain (Gondek et al, 2014). A recent study by Romanos et al (2019) highlighted that to reduce metals and pathogenic microorganisms in sludge in line with strict legislative limits, further processing (such as composting) may be required.…”
Section: Introductionmentioning
confidence: 99%